IMPLEMENTASI MAGANG PEMONDOKAN MAHASISWA UIN ANTASARI BANJARMASIN - Sari, Nyai Rukmana (ADDABANA: Jurnal Pendidikan Agama Islam, 2022)
ABSTRACT: The boarding internship is a program held by the Department of Islamic Religious Education at one of the well-known campuses in the city of Banjarmasin, namely UIN Antasari Banjarmasin. This boarding internship is one solution that is held for PAI students who are still lacking in reading skills (Qiraat, Tahsin, Tajwid) and writing the Qur'an. This study aims to describe the implementation of student boarding internships at the Department of Islamic Education, Faculty of Tarbiyah and Teacher Training at UIN Aantasari Banjarmasin 2016 from planning, implementation, as well as evaluation. In this study, the authors also want to know the supporting and inhibiting factors in the internship program. This study uses qualitative (field) research that is oriented or looks at the state of natural phenomena or symptoms. The research was conducted at the Al-Hikmah Islamic Boarding School in Kelayan A. The subjects were 2 program managers and 20 students of the 2016 Islamic Religious Education Department. The data collected by the researchers were observation, interviews and documentation. While in data processing used collection techniques, data editing and interpretation. The results showed (1) The application of student boarding internships went well, this was shown by careful planning, starting from testing PAI students by tahsin lecturers, recitation of the Qur'an in the course "Learning to Read and Write Al-Qur'an ” and it is also marked by the type of accommodation activities, the implementation of lodging activities that have been carried out by teachers who are experts in their fields and evaluations which are marked by the graduation of students in the Qur'anic tahsin and tajwid teaching courses, and accompanied by passing the PPL and KKN tests. (2) supporting factors are: a. Program indicators b. program manager. (3) inhibiting factors include: a. communication b. resources for the implementation of the student housing program.KEYWORDS: Implementation, Internship, Lodging.ABSTRAK: Magang Pemondokan adalah program yang diadakan oleh pihak jurusan Pendidikan Agama islam disalah satu kampus ternama diKota Banjarmasin yaitu UIN Antasari Banjarmasin. Magang Pemondokan ini merupakan salah satu solusi yang di adakan untuk mahasiswa PAI yang masih kurang dalam kemampuan bacaan (Qiraat, Tahsin,Tajwid) dan tulis Al-Qur’annya. Penelitian ini bertujuan untuk mendeskripsikan Implementasi magang pemondokan mahasiswa Jurusan Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Aantasari Banjarmasin Angkatan 2016, dari mulai perencanaan, pelaksanaan, juga dalam evaluasinya. Dalam penelitian ini juga penulis ingin mengetahui fator pendukung dan penghambat pada program magang tersebut. Penelitian ini menggunakan penelitian kualitatif (lapangan) yang berorientasi atau melihat pada keadaan fenomena atau gejala yang bersifat alami. Penelitian dilakukan di Pondok Pesantren Al-Hikmah di kelayan A. Dengan Subjek yaitu 2 pengelola program dan 20 Mahasiswa Jurusan Pendidikan Agama Islam angkatan 2016. Pengumpulan data yang peneliti adalah observasi, wawancara dan dokumentasi. Sedangkan dalam pengolahan data digunakan teknik koleksi, editing data dan interpretasi. Hasil penelitian menunjukan (1) Penerapan magang pemondokan mahasiswa berjalan dengan baik, hal ini ditunjukan dengan adanya perencanaan yang matang, mulai dari mentes mahasiswa PAI oleh dosen tahsin, tajwid Al-Qur’an dalam mata kuliah “Pembelajaran Baca Tulis Al-Qur’an” dan ditandai juga adanya jenis kegiatan pemondokan, pelaksanan kegiatan pemondokan yang telah dilakukan oleh pengajar yang ahli dibidangnya dan evaluasi yang ditandai dengan lulusnya mahasiswa pada mata kuliah pengajaran tahsin dan tajwid Al-Qur’an, dan disertai lulus tes PPL dan KKN. (2) faktor-faktor yang mendukung adalah:a. Indikator program b. pengelola program. (3) faktor-faktor penghambat diantaranya: a. komunikasi b. sumber daya pelaksanaan implementasi program pemondokan mahasiswa.KATA KUNCI: Implementasi, Magang, Pemondokan.